The posterior interosseous artery flap versus the adipofascial radial artery perforator flap in reconstruction of firecracker and homemade bomb blast injuries of the hand - Gupta, Madhumita; Jash, Prabir Kumar (International Surgery Journal, 2021)
Background: The soft tissues of the radial aspect of the hand are predominantly affected in firecracker and homemade bomb blast injuries. In such cases, regional flap options are quite appealing for defect coverage. We have compared the outcomes of using two pedicled regional forearm flaps in these injuries, the posterior interosseous artery flap (PIAF) and the adipofascial radial artery perforator flap (ARAPF). Methods: 37 patients underwent reconstruction of the hand with PIAF (20 cases) and ARAPF (17 cases) between January 2014 and December 2019. They were compared with regards to patient demographics, reconstruction techniques, short-term and long-term functional and aesthetic outcomes using the disabilities of the arm, shoulder and hand (DASH) score and the subjective satisfaction score (SSS). Results: All our flaps survived without any major complications affecting long-term outcome. We found no statistically significant difference between the two flaps in terms of patient demographics, flap paddle size, duration of hospital stay, DASH score and SSS for recipient site. However, significant difference was noted in the duration of surgery, method of donor site closure and SSS for the donor site. Conclusions: Both the PIAF and ARAPF can be considered in cases of soft tissue defects of the hand from firecracker or bomb blast injuries. Both preserve the major arteries of the hand while still having reliable vascular pedicle.